Banking regulation : does compliance pay? : evidence from Trinidad & Tobago - Seuraj, Simi ([Caribbean Centre for Money & Finance} [St. Augustine]TT, 2008)
Seeks to establish empirically whether complicance by an individual commercial bank in Trinidad & tobago with BCP 6-15 brings about any measurable improvement in performance by that bank.